Law No. 78 of the Year 2016 On Amending Some Provisions of the Penal Code = قانون رقم 78 لسنة 2016 بتعديل بعض أحكام قانون العقوبات - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic